Design Exploration of Inception Space for Dementia with Memory and Visuospatial Deficit - Muhammad Heru Arie Edytia; Mirza Irwansyah (Faculty of Engineering, Malikussaleh University, 2018)
The concept of inception space, perception, memory, scenario, layer, and labyrinth, is expected to affect the target (mark) as architectural space user by planting the idea 'secretly' in which the target is unaware of the intervention. Target who will undergo a process of inception is the person with dementia, people who have a progressive decline in cognitive function and behavior. The design methods are the nursing home case studies, the development of “slayer oranye”, and Qibla direction. The development of this method is done through the series model House of Ariadne and intervened in the old East sector of Universitas Syiah Kuala lecturer housing context, Banda Aceh. Results obtained is a concept of inception space as wayfinding for dementia with memory and visuospatial defici